2021
DOI: 10.1186/s13019-021-01684-8
|View full text |Cite
|
Sign up to set email alerts
|

Malignant primary pericardial mesothelioma presenting as effusive constrictive pericarditis: a case report study

Abstract: Background Primary pericardial mesothelioma (PPM) is a rare malignancy with a high prevalence of mortality. The diagnosis is usually challenging using a variety of imaging modalities and invasive procedures and is generally performed at the later stages of the disease or in autopsy. This case study points to an unconventional presentation of PPM and the challenges in diagnosing this rare mortal malignancy. Case presentation This study presents a 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…This case report describes a case of primary malignant pericardial mesothelioma with a survival of 2.5 years. This case has some points for discussion, as follows: (I) The most commonly misdiagnosed disease in PMPM is tuberculous pericarditis, where both pericardial lesions are similar, presenting as constrictive pericarditis, with pericardial tamponade and heart failure ( 6 ). When patients with pericardial effusion present with poor antitubercular concurrent with rapid effusion growth, the possibility of malignant mesothelioma of the pericardium needs to be considered, despite its low incidence and clinical rarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case report describes a case of primary malignant pericardial mesothelioma with a survival of 2.5 years. This case has some points for discussion, as follows: (I) The most commonly misdiagnosed disease in PMPM is tuberculous pericarditis, where both pericardial lesions are similar, presenting as constrictive pericarditis, with pericardial tamponade and heart failure ( 6 ). When patients with pericardial effusion present with poor antitubercular concurrent with rapid effusion growth, the possibility of malignant mesothelioma of the pericardium needs to be considered, despite its low incidence and clinical rarity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported positive autopsy rates of 0.006–0.0022% ( 4 , 5 ). Clinical manifestations include constrictive pericarditis, pericardial tamponade, and heart failure ( 6 ). Confirmation of the diagnosis relies on histopathological examination ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Primary cardiac malignancies are exceedingly rare, with a prevalence of 0.001% to 0.056% and account for 0.3% to 0.7% of all cardiac cancers. 36 Approximately 25% of primary cardiac tumors are malignant, with metastasis being 20 to 40 times more common than in primary malignant tumors. 3,37 Among primary malignant cardiac tumors, malignant pericardial mesothelioma is the third most common tumor after angiosarcoma and rhabdomyosarcoma, and is the most common primary malignant tumor of the pericardium.…”
Section: Malignant Pericardial Mesothelioma Introductionmentioning
confidence: 99%
“…Primary cardiac malignancies are exceedingly rare, with a prevalence of 0.001% to 0.056% and account for 0.3% to 0.7% of all cardiac cancers 36. Approximately 25% of primary cardiac tumors are malignant, with metastasis being 20 to 40 times more common than in primary malignant tumors 3,37.…”
Section: Introductionmentioning
confidence: 99%
“…Mesothelioma is an aggressive tumor characterized by local invasion and a poor prognosis ( 1 ). Most patients with mesothelioma have a history of exposure to asbestos, and there has been an upward trend in the incidence of mesothelioma in recent years in some areas ( 2 ).…”
Section: Introductionmentioning
confidence: 99%